In memoriam. Professor Mait Miljan (16.09.1939-1.16.2007). Mit Zusammenfassung - Sõrg, Mart (Estonian Discussions on Economic Policy, 2014)
I got to know Mait Miljan better in 1982 when the University of Tartu celebrated the 350th anniversary. Mait was one of the organisers. I then discovered that he had especially good organisational skills that became irreplaceable in developing the faculty work and were also very helpful in the foreign relations of our Faculty. He started his career as the marketing expert after graduating from Tartu University in 1963. In 1972 he successfully defended there his PhD in economics on the field of marketing. In 1974 he was elected as the Head of Department of Sales Management. He stayed on this position for ten years, during that period he became one of the best expert of sales management and marketing in Estonia. When the market economy was introduced in Estonia, there was no doubt that Mait Miljan was the best candidate to lead the newly created department of marketing. Virtually he had to start from scratch. His task was to develop a specialized programme of marketing studies and find new lecturers. He completed it successfully. As his achievements founding a new department were so impressive, then 1992 he was selected as the Deputy Dean in the faculty of Economics. His main research areas were the marketing management of the transition economy, value-based marketing management, cost and pricing, research and prediction of demand. He compiled two textbooks on these topics that helped several Estonian companies to shape their marketing strategy. He enjoyed doing research work together with his colleagues. His CV from the year 2005 counts 83 publications, from which the majority were written together with domestic and foreign co-authors. Mait always kept his word and was very accurate. It made it very pleasant attendingthe international conferences with him. Also he liked to live healthy and loved to do sports. He raised his children by these principles, organised lot of events for the family at his own-built cottage at Koolma Lake.He retired in 2005, but still had to continue teaching as a simultaneous retiring of the colleagues would otherwise have left too much teaching for younger teachers. The interests of the faculty and the department always came first for him. Unfortunately, he did not get to really enjoy his retirement as the beginning of 2007 he was diagnosed with cancer. Mait will be remembered as a hard-working, higly-principled poised man. Mait lives continously on both in my and my colleague´s memories.